Primary leiomyosarcoma of the scalp: a case report and review of the literature - Shuo Gao; Pule Liu; Jixing Liu; Wenzhen Yang; Shude Yang (Frontiers in Oncology)
Background and importanceLeiomyosarcoma is a rare and aggressive malignant tumor with a high potential for relapse and metastasis. Correct and timely diagnosis is critical for effective treatment, yet it is often challenging due to the diverse clinical presentations. This case report highlights the significance of early identification and the consequences of delayed diagnosis in scalp leiomyosarcoma.Clinical presentationWe present the case of a 39-year-old woman with a scalp neoplasm. Initially, the diagnosis was missed, leading to a delay in surgical intervention. The tumor demonstrated a locally aggressive course, infiltrating the skull and dura mater. Upon admission, the scalp tumor was promptly excised. This case provides valuable insights into the varied symptoms and presentations of scalp leiomyosarcoma, which can aid in the recognition of this condition.ConclusionThis report underscores the importance of considering leiomyosarcoma in the differential diagnosis of scalp masses, particularly when the etiology is unclear. Early recognition and intervention are essential to prevent locally invasive growth and potential metastasis, emphasizing the need for a high index of suspicion among healthcare professionals.